Global imbalances and the Revised Bretton Woods hypothesis: Wrong before the crisis and wrong after - Thomas I. Palley (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2013)
This paper explores and contrasts the revised Bretton Woods hypothesis (BW II) with the structural Keynesian hypothesis. Whereas the former sees the growing global imbalances of the three decades prior to the financial crisis of 2008 as beneficial, the latter sees them as problematic and destructive of shared prosperity in the United States. Moreover, the U.S. economic relationship with China is viewed as especially problematic as it involves the largest bi-lateral trade deficit, and because it has also been a major source of investment diversion and manufacturing job loss. The paper's conclusion is the BW II analogy between today's global financial system and the original Bretton Woods system is without foundation, but it survives because the hypothesis helps rationalize and justify large trade deficits and the process of corporate globalization.
urn:nbn:de:101:1-2013031310867
Keywords: F02; F32; F33; 330; Revised Bretton Woods hypothesis; Structural Keynesian hypothesis; global imbalances; U.S. trade deficit; Bretton-Woods-System; Keynesianismus; Wirtschaftliche Instabilität; Leistungsbilanz; USA